2018
DOI: 10.1002/ccr3.1791
|View full text |Cite
|
Sign up to set email alerts
|

Early experience of seven hepatocellular carcinoma cases treated with regorafenib

Abstract: Key Clinical MessageRegorafenib became second‐line treatment for the patients with sorafenib refractory. In our study, two patients could not continue regorafenib for its adverse effects. It was suggested that appropriate use criteria of regorafenib should be observed and manage adverse effects earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Regorafenib has been approved as a 2nd-line drug following sorafenib. We previously reported early experiences of 7 HCC patients treated with regorafenib [6]. Ogasawara et al [7] reported that the median of OS and median PFS with 2nd-line regorafenib were 17.3 and 6.9 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Regorafenib has been approved as a 2nd-line drug following sorafenib. We previously reported early experiences of 7 HCC patients treated with regorafenib [6]. Ogasawara et al [7] reported that the median of OS and median PFS with 2nd-line regorafenib were 17.3 and 6.9 months, respectively.…”
Section: Discussionmentioning
confidence: 99%